Preventing Surgical Complications during Pregnancy (International Journal of Food and Nutritional Sciences, 2022)
Background: As up to 2% of pregnancies are affected by nonobstetrical surgical complications, general surgeons are routinely visited for these challenges. This population only experiences concerns about the enhanced morbidity for pregnant patients and their unborn.Data sources: Through a Medline search and a review of applicable society and academy publications, a review of the English language literature pertaining to nonobstetrical surgical concerns was compiled.Conclusions: Current knowledge on many areas of surgical care for pregnant patients is reviewed in this paper. Anesthesiology, radiography, laparoscopy, and particular rare and common surgical disorders seen in pregnant patients are among the topics discussed.